Perancangan Sistem Informasi Geografis Pemetaan Peninggalan Belanda Di Kota Padang - restu, restu; Melladia, Melladia (STMIK Royal Kisaran, 2025)
Abstract: Padang City holds various historical relics from the Dutch colonial era, which possess significant historical value and high tourism potential. However, information regarding the locations and descriptions of these relics is still scattered and difficult to access in an integrated manner. This study aims to design and implement an Android-based Geographic Information System (GIS) that presents an interactive map containing the locations, descriptions, and photos of the heritage sites, along with a regional filter feature to facilitate navigation. The development process began with data collection from the Tourism Office and field observations, followed by map processing in ArcMap, publication to ArcGIS Online, and the creation of an Android application using ArcGIS Maps SDK and Jetpack Compose. Integration with a MySQL database allows the automatic display of location points on the map. The implementation results show that the application can display 33 heritage site points in three districts of Padang City, complete with descriptions, photos, district filters, and Web Map integration. Testing demonstrated that the application runs smoothly, is informative and interactive, and can support cultural preservation efforts while encouraging interest in historical tourism in Padang City. Keywords: geographic information system; dutch heritage; arcgis; android; padang city. Abstrak: Kota Padang menyimpan berbagai peninggalan bersejarah dari masa kolonial Belanda yang memiliki nilai sejarah dan potensi wisata tinggi. Namun, informasi mengenai lokasi dan deskripsi peninggalan tersebut masih tersebar dan sulit diakses secara terpadu. Penelitian ini bertujuan merancang dan mengimplementasikan Sistem Informasi Geografis (SIG) berbasis Android yang menyajikan peta interaktif berisi lokasi, deskripsi, foto peninggalan, serta dilengkapi fitur filter wilayah untuk memudahkan penelusuran. Proses pengembangan diawali dengan pengumpulan data dari Dinas Pariwisata dan observasi lapangan, dilanjutkan dengan pengolahan peta di ArcMap, publikasi ke ArcGIS Online, serta pembuatan aplikasi Android menggunakan ArcGIS Maps SDK dan Jetpack Compose. Integrasi dengan basis data MySQL memungkinkan penampilan titik lokasi secara otomatis pada peta. Hasil implementasi menunjukkan aplikasi mampu menampilkan 33 titik peninggalan di tiga kecamatan di Kota Padang, lengkap dengan deskripsi, foto, filter kecamatan, dan integrasi Web Map. Hasil pengujian membuktikan aplikasi berjalan lancar, informatif, dan interaktif sehingga dapat mendukung upaya pelestarian budaya, dan mendorong peningkatan minat wisata sejarah di Kota Padang. Kata kunci: sistem informasi geografis; peninggalan belanda;arcgis; android; kota padang